Odpowiedź:
a) x - x + 2 = 5
0 = 3
Równanie sprzeczne, brak rozwiązań
b) 2x + 4 = 2x - 4
2x - 2x = -4 - 4
0 = -8
Równanie sprzeczne, brak rozwiązań
c) 3x + 5 = 2x - 4
3x - 2x = -4 - 5
x = -9
d) 3x - 3 = 3x - 3
3x - 3x = -3 + 3
0 = 0
Równanie tożsamościowe, nieskończenie wiele rozwiązań
e) 7 - [tex]\frac{5}{2}[/tex] + [tex]\frac{3}{2}[/tex]x = 2x - 1 + 3x - 18
[tex]\frac{3}{2}[/tex]x - 2x - 3x = -1 - 18 + [tex]\frac{5}{2}[/tex] - 7 |×2
3x - 4x - 6x = -2 - 36 + 5 - 14
-13x = -47
x = [tex]\frac{47}{13}[/tex] = 3[tex]\frac{8}{13}[/tex]
f) 3 - 2x = [tex]\frac{x}{3}[/tex] + [tex]\frac{2}{3}[/tex] |×3
9 - 6x = x + 2
-6x - x = 2 - 9
-7x = -7
x = 1